1996
DOI: 10.1063/1.363725
|View full text |Cite
|
Sign up to set email alerts
|

Visible wavelength (6470 Å) GaxIn1−xP/GaAs0.66P0.34 quantum wire heterostructures

Abstract: Utilizing the strain-induced lateral-layer ordering (SILO) process, we have grown GaxIn1−xP multiple quantum wires (MQWR) on ternary GaAs0.66P0.34 substrates using a modified strain-balance mechanism. The resulting [110] lateral modulation occurred with a periodicity of ∼300 Å. Two dimensions of quantum confinement were obtained by surrounding the laterally confined GaxIn1−xP regions by layers of higher-energy-gap Al0.15Ga0.53In0.32P in the growth direction. A redshift in the photoluminescence emission was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Three 140 period (InAs) 13 /(GaSb) 13 superlattice structures were grown by molecular beam epitaxy (MBE) with both InAs and GaSb layers being nominally 40 Å. The SL's were intentionally grown with InSb interfacial bonds and details of the growth are given elsewhere 17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three 140 period (InAs) 13 /(GaSb) 13 superlattice structures were grown by molecular beam epitaxy (MBE) with both InAs and GaSb layers being nominally 40 Å. The SL's were intentionally grown with InSb interfacial bonds and details of the growth are given elsewhere 17 .…”
Section: Methodsmentioning
confidence: 99%
“…increases/decreases the bandgap and affects the polarization anisotropies. Generally, LCM is avoided in device structures; however, LCM combined with the unusual band line up of the InAs/GaSb superlattice system may lead to unique characteristics that may be beneficial for optoelectronic devices, in particular, quantum wire based detectors and lasers 6,7,[11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 It is also reported that the emission wavelengths of the SILO MQWR structures were changeable if a different number of SPS quantum wells or different growth temperatures were used. 4 Furthermore and most intriguingly, temperature-insensitive emission wavelengths were observed recently from In x Ga 1Ϫx As SILO MQWR heterostructures. 5 This temperature insensitive emission wavelength was attributed to a temperature induced multiaxial strain effect in the SPS regions.…”
mentioning
confidence: 87%
“…1 Based on this mechanism, Cheng et al [2][3][4] developed a straininduced lateral-layer ordering ͑SILO͒ process which strengthens this lateral composition modulation by growing short-period superlattices ͑SPSs͒ in the generic multiplequantum well ͑MQW͒ regions, and periodic regions with different compositions, or lateral quantum wells, were observed in the SPS quantum well regions along the growth plane. By combining the generic quantum wells in the growth direction, this SILO process has successfully fabricated In x Ga 1Ϫx As and In x Ga 1Ϫx P multiple-quantum-wire ͑MQWR͒ structures by growing (InAs) m /(GaAs) n and (InP) m /(GaP) n SPS on ͑001͒-oriented on-axis InP and GaAs substrates, respectively.…”
mentioning
confidence: 99%
“…In particular, light emitting diodes and lasers with compositionally modulated active regions have already been fabricated and have demonstrated modified materials performance in comparison to conventional quantum well lasers. [8][9][10] The causes of LCM are currently under debate, but it is generally agreed that there is a kinetic process in which surface diffusion, including a gradient term, together with strain lead to thickness undulation and composition modulation. 11 The detailed combination of these different effects is material dependent, and so it is possible that different mechanisms predominate in single-layer versus SPS structures.…”
Section: Introductionmentioning
confidence: 99%